Robust cloud management of MANET checkpoint sessions‡. (29th March 2016) - Alshareef, Hazzaa Naif; Grigoras, Dan
Summary: In a traditional mobile ad‐hoc network (MANET), if two nodes are engaged in a session and one of them departs suddenly, their communication is aborted. The session is not active anymore, work is lost, and consequently, the energy of the batteries which is a critical resource has been wasted. This paper proposes a model that uses a cloud service to register, save, pause, and resume sessions between MANET member nodes so that both the work in progress and energy are saved. A checkpoint technique is introduced to capture the progress of a session and allow it to be resumed. This is an additional service to our cloud management of the MANET. The model proposed in this paper was tested on Android‐based devices and an Amazon cloud instance. Experimental results show that the model is feasible, robust, and saves time and, more importantly, energy if session breaks occur frequently. We have also enhanced the authentication process by using a two‐way authentication method to provide a high level of protection when accessing system services. Copyright © 2016 John Wiley & Sons, Ltd.